1999
DOI: 10.1017/s0014479799354089
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of degraded grasslands in north Syria: use of farmer participatory research to encourage the sowing of annual pasture legumes

Abstract: A series of experiments on communally-owned grasslands in the barley±livestock zone of north Syria were conducted to test the hypothesis that introduction of Mediterranean annual legumes will increase productivity. The experiments were preceded by a survey to determine farmers' attitudes, describe the farming systems and to select appropriate collaborators. The ®rst experiment examined the establishment of medics (Medicago spp.) and clovers (Trifolium spp.) distributed by hand, and monitored their eects on bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…This may be due to species differences, as cowpea varieties generally already have a high tolerance for low nutrient soils, compared to common bean varieties that have limited tolerance for edaphic stresses (Snapp et al, 1998A;Wortmann et al, 1995). A number of researchers have suggested that only relatively well-off farmers have a strong interest in, and sufficient resources, to invest in soil ameliorating practices (Ghassali et al, 1999;Witcombe, 1999). For example, one village out of 11 in Northern Syria was found to have adequate resources and other traits -necessary but not sufficient conditions for them to rehabilitate degraded areas through seeding legumes (Ghassali et al, 1999).…”
Section: Farmer Perceptions Of Returns and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to species differences, as cowpea varieties generally already have a high tolerance for low nutrient soils, compared to common bean varieties that have limited tolerance for edaphic stresses (Snapp et al, 1998A;Wortmann et al, 1995). A number of researchers have suggested that only relatively well-off farmers have a strong interest in, and sufficient resources, to invest in soil ameliorating practices (Ghassali et al, 1999;Witcombe, 1999). For example, one village out of 11 in Northern Syria was found to have adequate resources and other traits -necessary but not sufficient conditions for them to rehabilitate degraded areas through seeding legumes (Ghassali et al, 1999).…”
Section: Farmer Perceptions Of Returns and Constraintsmentioning
confidence: 99%
“…A number of researchers have suggested that only relatively well-off farmers have a strong interest in, and sufficient resources, to invest in soil ameliorating practices (Ghassali et al, 1999;Witcombe, 1999). For example, one village out of 11 in Northern Syria was found to have adequate resources and other traits -necessary but not sufficient conditions for them to rehabilitate degraded areas through seeding legumes (Ghassali et al, 1999). Only the wealthiest group of farmers in a Mali case study invested in soils through improved residue recycling (Defoer et al, 1998).…”
Section: Farmer Perceptions Of Returns and Constraintsmentioning
confidence: 99%
“…for use in dry areas where rainfall is between 250 and 350 mm. These areas are found between the steppe and high‐potential cereal‐growing regions in WANA, have a very fragile agro‐ecosystem and are currently threatened by further degradation and erosion because of the increasing annual cropping of barley in response to increasing population pressure (Ghassali et al ., ; Ryan et al ., ; Louhaichi et al ., ). However, there is an opportunity for the introduction of drought‐ and/or cold‐tolerant annual feed‐legume species, such as Vicia spp.…”
Section: Mediterranean Forage Legumesmentioning
confidence: 99%
“…The objectives were to monitor the effects of stocking rate and phosphate fertilizer on Mediterranean grassland, measure the response of livestock production to phosphate application, assess the carrying capacity of native vegetation, and identify botanical indicators of overgrazing. 12 Since then, research has progressively expanded in the arid and semiarid countries of CWANA, focusing on seed bank dynamics, community-based rangeland rehabilitation, 13 palatability of Mediterranean shrubs, 14 germplasm collection of native range species, 15 rangeland biodiversity characterization, 16 and impacts of short-term protection from grazing (resting technique), which gave remarkable results on plant cover dynamics and productivity. 17,18 Research conducted within the Mashreq-Maghreb project highlighted the importance of property rights, 19 policy options, 20 and social and institutional aspects.…”
Section: Review Of Past Strategymentioning
confidence: 99%